(untitled) (Journal of Comparative & International Higher Education, 2024)
In the past two decades, the Government of Pakistan has significantly invested in higher education (HE) to bring structural reforms in funding, governance, and quality assurance mechanisms. Their overarching mission has been to fuel national socioeconomic development by ensuring equal access to HE. Given this, the present study aimed to address the following research question: To what extent have current HE reforms in Pakistan enabled equitable access to HE? To address this question, this study drew from a social justice-centered framework to track trends in HE access that is, broadly and based on socio-economic status, gender, urbanicity/rurality, and region/province. Using secondary data from diverse sources including the HEC, Academy of Education Planning and Management, and the Pakistan Poverty Alleviation Fund, we conducted descriptive longitudinal analyses. Findings underscore that the system has failed to provide equal access to HE in several ways and discuss some possibilities for policymakers in equalizing the opportunities.